The influence of the dimensions of perfectionism on the formation of emotional maladjustment - Savina, Maiia V.; Malakhovetska, Mariia O. (Psychiatry, Neurology and Medical Psychology, 2021)
The growing complexity of the medical profession places increased demands on the future physician’s adaptive capacity. The problem of the relationship of the aff ective spectrum disorders with such a dysfunctional personality trait as perfectionism is intensively discussed in clinical psychology. Medical students are in a more diffi cult position than others. It’s related to their future profession requires a high level of training and also associated with a high responsibility for the lives and patient’s health. High pace, intense workload, stress of life makes increased demands on the compensatory mechanisms of the medical student’s psyche, failure of which leads to psychological and social confl icts. The paper presents an empirical study of the severity of symptoms of depression, anxiety, and daily stress as the main components of emotional maladaptation, depending on the level of perfectionism in the medical student environment in conditions of increased psychological stress and pre-examination stress. Subjects with a low level of perfectionism are as emotionally prosperous as possible - they have no signs of depression in 89% of cases. In the group of subjects with a medium level of perfectionism, the number of respondents in whom there are no signs of depression decreases and the number with mild, moderate and high levels of depression increases. In the group with a high level of perfectionism, the number of people without signs of depression is half of the whole group, a sharp increase in the number of subjects with moderate and high levels of depression. The level of depression in all three groups is statistically signifi cantly diff erent from each other: the lowest in the group with a low level of perfectionism and the highest in the group with a high level of perfectionism (p <0.001). Positive correlations between the general indicator of perfectionism, its separate parameters and indicators of depression, anxiety and daily stress in the studied groups are revealed. The data obtained as a result of the study confi rm the high level of emotional maladaptation of medical students. In the academic student medical environment, respondents with a pronounced level of perfectionism experience more high-intensity, daily stress (both in the interpersonal and academic spheres of student life) compared to respondents with moderate and low levels of perfectionism.